Charge characteristics of soil organic matter fractions in a Ferric Lixisol under some multipurpose trees - Oorts, K.; Vanlauwe, Bernard; Cofie, Olufunke O.; Sanginga, N.P.; Merckx, Roel (2000)
Soil organic matter (SOM) has a key role in maintaining soil fertility in weathered soils in the tropics. This study was conducted to determine the contribution of different SOM fractions to the cation exchange capacity (CEC) of a tropical soil as influenced by organic matter inputs of different biochemical composition. Soil samples were collected from a 16-yr old arboretum established on a Ferric Lixisol, under five multipurpose tree species: Leucaena leucocephala, Dactyladenia barteri, Afzelia africana, Pterocarpus santalinoides, and Treculia africana. Fractions were obtained by wet sieving and sedimentation after dispersion with Na2CO3. Fractions larger than 0.053 mm were separated into mineral and organic components by flotation on water. Relationships between CEC and pH were determined using the silverthioureum-method. For all treatments the organic fractions had the highest CEC, expressed on a dry matter basis, and the CEC of the fractions smaller than 0.053 mm was inversely related to their particle size: clay (< 0.002 mm) > fine silt (0.002–0.02 mm) > coarse silt (0.02–0.053 mm). A positive correlation (significant at the 0.01 probability level) existed between the slope of the fitted CEC-pH relationships and the organic C concentrations of the whole soil and both silt fractions. The clay and fine silt fractions were responsible for 85 to 90% of the CEC of the soil. Organic inputs with a high C/N and lignin/N ratio produced fine and coarse silt sized SOM fractions with the highest charge density. Therefore, inputs of slowly decomposing organic residues seem to be promising for increasing the CEC of highly weathered soils.